POWER AND SEXUALITY IN HENRIK IBSEN‟S GHOSTS - Md. Amir Hossain; Vlera Ejupi; Arburim Iseni; Liljana Siljanovska (European Scientific Journal, ESJ, 2014)
This paper aims to examine Henrik Ibsen‘s Ghosts in the light of hisattitude towards the hollowness of traditional Bourgeois marriage and familylife. It looks at brutality, falsehood, deception, irrationality, and above all,matriarchal sexual subjugation, and oppression through the patriarchal powerand domination between individuals of the 19th century ScandinavianBourgeois society. This paper is explained by expressing the assumptions ofFoucauldian and Belseyian theory of power and sexuality, and Women inPower in the Early Modern Drama by Jankowski and Freudian theory of sexand venereal disease syphilis, Menckenian concepts of gender and sexuality,Northam‘s viewpoint on Mrs. Alving‘s inner struggle, and FrancisFerguson‘s criticism on the personality of Pastor Manders and Engstrand.This paper also explicates Captain Alving as a symbol of a dissolute,drunkard, libertine, rakish, sinful and masochistic behavior. Mrs. Alving hasbeen shown as a self-respective, self-egotistic, self-revolutionary figure inthe name of social duty and responsibility for which she always concealsherself in fear of outer stigma and scandal. Both Johanna and Regina are theembodiments of the 19th century Norwegian oppressive and degenerativefeminism, and Oswald as a cursed and born victimized self of hereditarydisease. Both Pastor Manders and Engstrand are symbol of immorality,hypocrisy, stupid respectability and psychological crookedness. Throughplot-structure, dramatic technique, and art of characterization, Ibsen‘s purpose is to expose everyday problems of Scandinavian women includingpsychological conflicts, human dilemma, global right and suffrage of femalein the modern society.